Konieczność i możliwości twórczej aktywności w procesie poznawania dzieła literackiego na lekcji = The necessity and possibility of creating activity in the cognitive process of a literary work during lessons - Dittmann, Gerhart (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper introduces and motivates possibilities of creating works by the teacher and the students in the cognitive process of a literary work during lessons. The author especially treats of a) the purpose of creating activity, b) its object, c) conditions and connections between the structure of the creating process and the creating activity.
Keywords: dzieło literackie; aktywność twórcza; nauczanie